FEAR THIS MAN. - Kushner, David (Foreign Policy)
The article discusses Hisham Almiraat, editor of pro-democracy website Mamfakinch. Topics discussed include citizen journalists, Moroccan activists and David Vincenzetti, chief executive officer of Hacking Team. Other topics which includes terror attacks in Madrid, Spain on March 11, 2004, security industry and software Remote Control System (RCS) by the Hacking Team are also discussed. Further, topics including national security, hacker activists and human rights are also discussed. In addition, privacy is mentioned.